Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1742-481x.2012.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of diabetic foot ulcers: prospective follow‐up analysis in the Eurodiale subgroup

Abstract: Few studies have examined factors associated with diabetic foot ulcer (DFU) recurrence. Using data from patients enrolled in the prospective Eurodiale DFU study, we investigated the frequency of and risk factors for DFU recurrence after healing during a 3-year follow-up period. At our site, 93 Eurodiale-enrolled patients had a healed DFU. Among these, 14 were not alive; of the remaining 79 patients we enrolled 73 in this study. On entry to the Eurodiale study, we assessed demographic factors (age, sex and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
127
3
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 32 publications
6
127
3
6
Order By: Relevance
“…Total incremental costs in the year postindex date increase from $11,710 to $18,756 for Medicare and from $16,883 to $31,851 for private insurance when these severely sick or costly patients are retained (data not shown). Third, the objective of this analysis was to estimate the annual burden associated with DFU; however, it should be noted that prior research has found that many patients remain unhealed after 12 months (16) and/or experience reulceration (17). As a result, the estimates of this study understate the true incremental costs associated with a DFU episode, and further research is warranted to examine the potentially large costs of DFU beyond the first year.…”
Section: Discussionmentioning
confidence: 65%
“…Total incremental costs in the year postindex date increase from $11,710 to $18,756 for Medicare and from $16,883 to $31,851 for private insurance when these severely sick or costly patients are retained (data not shown). Third, the objective of this analysis was to estimate the annual burden associated with DFU; however, it should be noted that prior research has found that many patients remain unhealed after 12 months (16) and/or experience reulceration (17). As a result, the estimates of this study understate the true incremental costs associated with a DFU episode, and further research is warranted to examine the potentially large costs of DFU beyond the first year.…”
Section: Discussionmentioning
confidence: 65%
“…However, our annual incidence is higher than that observed in developed countries, where a dramatic reduction in the rate of diabetic foot has been recorded over the past two decades [8,25,26]. The North-West and West of Ireland diabetic foot studies conducted in the United Kingdom and the Republic of Ireland reported diabetic foot incidence of 2.2% and 2.6%, respectively [8,27]. Similarly, Muller et al and de Sonnaville et al both from the Netherlands indicated an incidence of 2.1% and 1.8%, respectively [28,29].…”
Section: Discussionmentioning
confidence: 89%
“…The end result of these disrupted repair networks is the defective quality of repaired tissue (as validated with histologic, molecular, and biomechanical testing), which may underlie the propensity for chronic wound recidivism. 45,46,48 Importantly, this study provides a molecular basis for excessive dermal proteolysis in chronic wounds and indicates the importance of ongoing efforts to target the mechanical environment to aid in wound repair. 39,49,50 Copyright © 2013 Lippincott Williams & Wilkins.…”
Section: Discussionmentioning
confidence: 97%